Does Work-Family Conflict Mediate the Associations of Job Characteristics With Employees’ Mental Health Among Men and Women? - Carvalho, Vânia S.; Chambel, Maria J.; Neto, Mariana; Lopes, Silvia (Frontiers in Psychology, 2018)
Job characteristics are important to work-family conflict (WFC). Additionally, is well established that WFC has a negative impact on mental health. As such, this research aims to examine the role of WFC as a mechanism that explains the relationship between job characteristics (i.e. those establishing by the Job Demands-Control-Support Model) and workers’ mental health. Moreover, based on gender inequalities in work and non-work roles, this study analyzed gender as moderator of this mediation. Specifically, the relationship between job characteristics and WFC and the relationship between WFC and mental health could be stronger for women than for men. With a sample of 254 workers from a Portuguese services company, (61% males), and based on a multiple-group analysis, the results indicated that the WFC mediates the relationship between job characteristics (i.e. job demands, job control) and mental health. It was reinforced that job demands and lack of control could contribute to employees’ stress and, once individual’ energy was drained, the WFC could emerge. Ultimately, may be due to the presence of this conflict that individuals mental health’ is negatively affected. Contrary to our expectations, this relationship is not conditioned by gender (Z-scores were non-significant). The study results have implications for human resource management, enhancing the knowledge on the relationship between the WFC and workers’ mental health.